Implementación de buenas prácticas de manufactura para el mejoramiento de la calidad microbiana del yogurt tipo I de la microempresa O’campo - Vera Hernández, Laila Brigitte (2024)
The objective of this research was to implement Good Manufacturing Practices (GMP) to improve the microbial quality of type I yogurt from the O'campo microenterprise, located in Chone canton. A compliance list was used to obtain an initial diagnosis of the microenterprise where 58.54% compliance and 41.46% non-compliance were obtained, then three samples of yogurt (pitahaya, strawberry and pineapple) were taken to analyze the microbial load as established by NTE INEN 2395 (total coliforms, Escherichia coli, Mold and yeast count) where they did not comply with what was established. Therefore, the GMP manual was designed in accordance with the criteria established in resolution ARCSA-DE-067-2015-GGG. Subsequently, the staff was trained and the GMP was implemented in the microenterprise, then the post-implementation list was applied, obtaining 86.59% compliance. Then the microbial load in the yogurt samples was analyzed, being within the limits allowed by the NTE INEN mentioned above. Finally, a statistical analysis of the T-student was carried out on the compliance list, resulting in a significance level of <0.001, accepting the alternative hypothesis, while in the chi square test when comparing the results obtained from the microbiological analyzes pre and post implementation of the GMP, indicating that the microbiological quality of type I yogurt (pitahaya, strawberry and pineapple) is highly significant because the microbial load in the product of the microenterprise was reduced by implementing Good Manufacturing Practices.